Frost jacking characteristics of steel pipe screw piles for photovoltaic support foundations in high-latitude and low-altitude regions - Gongliang Liu; Shaojie Fu; Xuefeng Zhao; Wei Jiang; Dong Li; Shibo Fu (Soils and Foundations, 2023)
In this study, the frost jacking characteristics of steel pipe screw piles for photovoltaic support foundations in high-latitude and low-altitude regions are studied via in situ tests and numerical simulations. The elevation changes in 7 in situ test piles during a frost heave cycle are monitored, and the observation results are used to verify the accuracy of the finite element model. The frost jacking with different helix spacings is studied, and the anti-frost jacking abilities of piles coated with different thicknesses of asphalt are analysed. The results show that the annual frost jacking values of the piles are approximately 6.08 ∼ 7.73 mm in the helix spacing range of 500 ∼ 700 mm. The value of 675 mm used in the actual project is the smallest, and the cumulative jacking during the service life is approximately 144.68 mm. The asphalt coating on the pile body can reduce the interaction between the frozen soil and the pile. Asphalt coatings larger than 10 mm basically eliminate the frost jacking of the pile. This research provides reliable design suggestions for helix spacing design and anti-frost jacking measures of screw piles in similar projects.